2018
DOI: 10.1002/1873-3468.13102
|View full text |Cite
|
Sign up to set email alerts
|

Sensing and transducing forces in plants with MSL10 and DEK1 mechanosensors

Abstract: Mechanosensitive (MS) channels behave as microprobes that transduce mechanical tension into electric and ion signals. The plasma membrane anion-permeable channel AtMSL10 belongs to the first family of MS channels (MscS-LIKE) that has been characterized in Arabidopsis thaliana. In the same membrane, a rapidly activated calcium MS channel activity (RMA) associated with the presence of the DEFECTIVE KERNEL1 (AtDEK1) protein has been recently described. In this Review, based on the comparison of the specific prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 57 publications
(134 reference statements)
0
19
0
Order By: Relevance
“…This allows entry of ions such as calcium in the cell, and changes in ion intracellular concentration can then be sensed. Plants possess various types of plasma membrane stretch-sensitive ion channels (Figure 2) including the McS-Like (MSL), Mid1-Complementing Activity (MCA), Two Pore Potassium (TPK), Reduced hyperosmolarity-induced [Ca 2+ ] increase (OSCA), Piezo and possibly Defective Kernel1 (DEK1) (Hamant and Haswell, 2017; Guerringue et al, 2018). Experimental work has shown that some of them are indeed involved in mechanosensing.…”
Section: Putative Mechanosensorsmentioning
confidence: 99%
“…This allows entry of ions such as calcium in the cell, and changes in ion intracellular concentration can then be sensed. Plants possess various types of plasma membrane stretch-sensitive ion channels (Figure 2) including the McS-Like (MSL), Mid1-Complementing Activity (MCA), Two Pore Potassium (TPK), Reduced hyperosmolarity-induced [Ca 2+ ] increase (OSCA), Piezo and possibly Defective Kernel1 (DEK1) (Hamant and Haswell, 2017; Guerringue et al, 2018). Experimental work has shown that some of them are indeed involved in mechanosensing.…”
Section: Putative Mechanosensorsmentioning
confidence: 99%
“…Thus, one straightforward interpretation of the data presented here is that cell swelling increases membrane tension, which opens the MSL10 channel and provides an ionic signal that activates the rest of the downstream pathway. However, MSL10 has a preference for anions, and electrophysiological experiments with large ions suggest that it does not conduct Ca 2+ [46,47,91]. As MSL10 has a relatively long closing time [47], one possibility is that an extended release of Cl À ions through the MSL10 channel pore leads to depolarization of the plasma membrane and the subsequent activation of depolarization-activated Ca 2+ channels [92].…”
Section: Msl10 As a Cell Swelling Sensormentioning
confidence: 99%
“…There is no direct experimental evidence that DEK1 has an intrinsic Ca 2+ channel activity, although it remains possible. However, DEK1 may interact with other Ca 2+ transporters such as Piezo‐type (Tran et al , ; Guerringue et al , ) and thus affect RMA Ca 2+ intake. In any case the signal perceived by DEK1 appears to be related to differential membrane tension at the surface of the cell (Malivert et al , ).…”
Section: Introductionmentioning
confidence: 99%